(untitled) (Mūzikas akadēmijas raksti, 2024)
The neoromanticism proves to be a characteristic trend in the contemporary Latvian symphonic music. This style is preserving and developing the ideas of new simplicity, new sensuality, new tonality and new romanticism, which emerged in the 70s of the 20th century. As to the conceptual level modern Latvian symphonic music is dominated by a wide range of powerful contrasts. The system of musical images of the neoromanticism is rich in both a more universal scope means of expression and belief in ethic ideal. Such a line is typical for the symphonies written in the 90s of the 20th century by such composers as Arturs Maskats, Juris Karlsons, Pēteris Vasks and Andris Vecumnieks. This music carries on the tradition of the so-called great symphony, pioneered in the 19th century by such luminaries as L. van Beethoven, J. Brahms, A. Bruckner, G. Mahler and F. Schubert and continued in the 20th century by such masters as Jānis Ivanovs, W. Lutoslawski and D. Schostakovich. In general it is possible to single out.